COVID-19 Exposure Among First Responders in Arizona. Issue 12 (December 2020) - Shukla, Vershalee; Lau, Christine S.M.; Towns, Mikayla; Mayer, Jennifer; Kalkbrenner, Kara; Beuerlein, Steve; Prichard, Pablo
Abstract : Objective: The number of COVID-19 cases in Arizona is rapidly increasing, leading the country in the rate of new daily cases. Exposure among first responders remains unknown. Methods: Rates of SARS-CoV-2 IgG among first responders in Arizona were determined, and attitudes/views about the impact of COVID-19 on their work life was analyzed. Results: Of 3326 first responders, 50 (1.50%) tested positive for SARS-CoV-2 IgG. Most first responders thought antibody testing would help ease their anxieties (62.5%) and be beneficial to their work-life (60.6%). Conclusion: The rate of COVID-19 exposure among first responders in Arizona is low—1.50%. COVID-19 is a concern among many of the first responders, and antibody testing was beneficial in easing their anxieties about going to work and performing work-related duties. Abstract : Supplemental Digital Content is available in the text